On the tribal classification of the Nearctic Melolonthinae (Coleoptera: Scarabaeidae), with descriptions of new species of Acoma Casey, 1889 - Evans, Arthur V.; Smith, Andrew B.t. (Zootaxa, 2020)
The subfamily Melolonthinae (Coleoptera: Scarabaeidae) is defined and characterized, and a brief summary of the world melolonthine tribes and their distributions are provided. Nearctic genera previously considered incertae sedis (Acoma Casey, 1889, Chaunocolus Saylor, 1937 and Chnaunanthus Burmeister, 1844, Phobetus LeConte, 1856, and Warwickia Smith & Evans, 2005) are each placed in the proposed new tribes Acomini, Chnaunanthini, Phobetusini, and Warwickiini, respectively. Tribal assignments for all Nearctic melolonthine genera are presented. Acoma chihuahuaensis, A. eusexfoliata, A. nonglabrata, and A. pararobusta are all new species described from Mexico. The only known example of a female Acoma, represented by a specimen of A. knulli Howden, 1958, is figured and characterized. The generic composition of the Nearctic Melolonthini and Rhizotrogini is examined. Madiniella Chalumeau & Gruner, 1976, previously placed in Tanyproctini, is transferred to Rhizotrogini. The subfamilies Oncerinae and Podolasiinae are each removed as tribes from the Melolonthinae and elevated to the subfamily level within Scarabaeidae. The subtribe Triodonina is placed in synonymy with the tribe Rhizotrogini. An updated generic checklist and tribal key of the Nearctic Melolonthinae are provided.